2014
DOI: 10.1039/c4cc05730a
|View full text |Cite
|
Sign up to set email alerts
|

Tandem catalysis: a new approach to polypeptides and cyclic carbonates

Abstract: A new tandem catalytic system mediates very efficiently and selectively at room temperature two sequential reactions to produce relevant derivatives in one pot. Remarkably, this new concept of catalysis allows the facile synthesis of polypeptides and provides direct access to cyclic carbonates in high yields, through the incorporation of the carbon dioxide released from the initial step, thus achieving full-atom economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…As depicted in Figure , the formation of the mono(alkoxide) species (salen)Al(OR) resulting from the insertion of PO into an AlCl bond can occur, similarly to what was reported in the PO/CO 2 copolymerization or in the ROP of NCAs . Although we demonstrated that the mono(alkoxide) species is efficient for NCA polymerization, neutral aluminum alkoxide derivatives are inactive at room temperature for the ROP of lactide.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…As depicted in Figure , the formation of the mono(alkoxide) species (salen)Al(OR) resulting from the insertion of PO into an AlCl bond can occur, similarly to what was reported in the PO/CO 2 copolymerization or in the ROP of NCAs . Although we demonstrated that the mono(alkoxide) species is efficient for NCA polymerization, neutral aluminum alkoxide derivatives are inactive at room temperature for the ROP of lactide.…”
Section: Resultssupporting
confidence: 85%
“…The high polymerization activities observed with the salen aluminum complex Al ‐ 1 ( Figure ) led us to use the same reaction conditions for the ring‐opening copolymerization of NCA and rac ‐LA . Therefore, the catalytic system was pre‐activated in the presence of 2 eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 In pioneering earlier work, Thomas and co-workers demonstrated that N-carboxyanhydride ROP could be used to produce polypeptides and the released CO 2 was subsequently used to make cyclic carbonates via tandem catalysis. 24 Inspired by this intriguing recycling opportunity and with polymerisation catalysts in hand known to operate under low CO 2 pressures, 22,23 we envisaged a single catalyst could be used in a switchable process to deliver block polymer product (Scheme 1).…”
mentioning
confidence: 99%
“…Recently, the selective and efficient conversion of light olefins with CO 2 as a C 1 building block into value-added enantiomerically pure cyclic carbonates has attracted great interest from chemists and governments due to its tremendous potential economic and environmental impact, especially considering the increasing worldwide greenhouse effect 1 . The general synthetic procedure includes two mechanistically distinct catalytic processes consisting of the asymmetric epoxidation of olefins, based on the research of Sharpless and others, and the asymmetric coupling epoxide with CO 2 (refs 2 , 3 , 4 , 5 ).…”
mentioning
confidence: 99%